Carbon-MEMS based rectangular channel microarrays embedded pencil trace for high rate and high-performance lithium-ion battery application. Issue 23 (13th October 2021) - Gangadharan, Ananya; Kali, Suresh; Mamidi, Suresh; Pathak, Anil D.; Sharma, Chandra S.
Abstract : C-MEMS based rectangular channel microarrays anode for high performance Li-ion battery. Abstract : The miniaturization of a lithium-ion battery has been an aspiration in portable electronic devices and a possible method of implementation is by changing the electrode configuration from a 2D system to a 3D one. A carbon microelectromechanical system is a plausible execution of lithium-ion storage from 2D carbon films to 3D structures. However, the use of semiconducting silicon as a substrate for 3D structures and dendrite formation are hurdles. The present work describes the fabrication of 3D carbon rectangular channels on a pencil-traced stainless steel current collector and its utilization as the anode in a lithium-ion battery. Detailed physical and electrochemical studies demonstrate the advantage of this electrode in terms of reversible storage capacity and the establishment of a low resistance path for an electrochemical reaction. The cell exhibits an extraordinary capacity of 2000 mA h g −1 at 150 mA g −1 and it retained a capacity of ∼400 mA h g −1 even at 10 000 mA g −1 after 1750 cycles. Also, the full-cell prototype further proves the potency of this electrode. Additionally, the time-dependent Li-ion concentration gradient across the 3D carbon rectangular channels is estimated using a diffusion-limited model. These simulation studies clearly suggest that Li-ion diffusion is more favorable in 3D carbon rectangular channels than in 2D films.